PENGARUH PEMBERIAN TEPUNG SEREH MERAH SEBAGAI ANTIBIOTIK ALAMIAH TERHADAP KONSUMSI DAN KECERNAAN NUTRISI KAMBING KACANG BETINA (The effect of lemongrass powder as a natural antibiotics on intake and digestibility nutrient of kacang goat) - Leady H.S. Ratu; Gusti Ayu Yudiwati Lestari; Mariana Nenobais (Universitas Nusa Cendana, 2020)
The aim of this research was to determined the effect of lemongrass powder as a natural antibiotic on intake and digestibility of DM, OM, CP and TDN of females Kacang goat fed hay Kume grass. Four female kacang goats with 6-10 months old and initial body weight of 10 kg was used. Experiment research method was used with latin square design 4x4 as reseach design. The treatments, i.e. 70% hay + 30% concentrate + lemongrass powder with different levels, 70% hay kume grass + 30% concentrate + S0, S0 + 10gr lemongrass powder = S10; S0 + 20gr lemongrass powder = S20; S0 + 30gr lemongrass powder = S30; Data was analysed used anova and the data showed significant was tasted with Duncan. The variabels measured were intake and digestibility dry matter, organic matter, crude protein and total digestible nutrient. The result showed that lemon grass powder providing as concentrate component was followed by increase of dry and organic matter consumption, crude protein consumption and digestibility, while digestibility of dry and organic matter and true digestible nutrient was decrease. Statistical analysis showed that the treatment had significant effect (P<0,05) on crude protein digestibility, while no significant effect (P>0,05) on intake and digestibility of dry and organic matter, crude protein consumtion and total diigestble nutrient. It can be concluded that lemon grass powder providing with different levels had the same effect on consumption and digestibility of nutrients except digestibility value of crude protein.